Vegetation Types, Climatic Conditions and Trigona sp. Honey Quality in Onewila Village, Ranomeeto District South Konawe Regency - Aminuddin Mane Kandari; Zakiah Uslinawaty; Muh. Ilton (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Kandari AM, Uslinawaty Z, Ilton M. 2020. Vegetation types, climatic conditions and Trigona sp. honey quality in Onewila Village, Ranomeeto district South Konawe Regency. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1):57-63.Forests in Indonesia have considerable potential because besides being used in the form of wood for various purposes, it also has the potential of non-timber products that can be used for various things, one of which is as a vegetation for honey bees, especially bees Trigona sp.This study aims to identification of vegetation types, climatic conditions and honey quality of Trigona sp. in the Onewila village, Ranomeeto District South Konawe Regency. The observed variables were vegetation, temperature, rainfall, and honey quality based on SNI 2013 standards. The results found the vegetation types at the cultivation location was Caliandra (Caliandra calothyrsus =10), coconut (Cocos nucifera = 12), teak (Tectona grandis= 20), peat (Syzygium polycephalum Merr = 7), mango (Mangifera indica =5), langsat (Lansium domesticum =15), kedondong (Spondias dulcis =3), guava (Psidium guajava =4), areca (Areca catechu = 10), coffee (Coffea Arabica = 15), cashew nut (Anacardium occidentale =15), areca nut (Areca catechu), coffee (Coffea arabica), cashew nut (Spondias dulcis), Cashew nut (Anacardium occidentale = 15), Sirsak ((Annona muricata = 2), and asoka flowers (Saraca asoka= 5). The air temperature and rainfall conditions in the location is very supportive of Trigona cultivation because the average of air temperature ranges from 29oC, and the average monthly rainfall at Ranomeeto station is highest in January (135 mm) and lowest in August (16.8 mm). The honey quality of Trigona sp, from several variables such as water content, acidity, HMF levels, and reducing sugar levels are 16.98%, 33.94 mg/kg, 17.3 mg/kg, 69.31 % b/b. This means that the honey quality of Trigona sp found in Onewila village meets the Indonesian National Standard (SNI 01-3545-2013 2013).